2021
DOI: 10.2147/ijgm.s292894
|View full text |Cite
|
Sign up to set email alerts
|

The Sagittal Parameters and Efficacy of Pedicle Subtraction Osteotomy in Patients with Ankylosing Spondylitis and Kyphosis Under Different Lumbar Sagittal Morphologies

Abstract: Objective This study aimed to compare the changes in sagittal parameters and the efficacy of pedicle subtraction osteotomy (PSO) in patients with ankylosing spondylitis (AS) and kyphosis under different lumbar sagittal morphologies and to explore the effect of sagittal morphology on the selection of PSO levels. Methods A total of 24 patients with AS and thoracolumbar kyphosis (TK) who were admitted to the First Affiliated Hospital of Xinjiang Medical University between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Zhang et al . 31 demonstrated that PSO at L2/L3 achieved the greatest corrective success in patients with AS with lumbar kyphosis. We also assumed that PSO using the MI technique would be more suitable at the L2/L3 level.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Zhang et al . 31 demonstrated that PSO at L2/L3 achieved the greatest corrective success in patients with AS with lumbar kyphosis. We also assumed that PSO using the MI technique would be more suitable at the L2/L3 level.…”
Section: Discussionmentioning
confidence: 92%
“…This allowed for consideration of the correction of thoracolumbar kyphosis and reconstruction of the lumbar lordosis. Zhang et al 31 demonstrated that PSO at L2/L3 achieved the greatest corrective success in patients with AS with lumbar kyphosis. We also assumed that PSO using the MI technique would be more suitable at the L2/L3 level.…”
Section: Applicability Of Mini-open Pso For As-related Spinal Kyphosismentioning
confidence: 99%
“…Most PSOs reported in the literature are generally performed in the apical lumbar lordosis region (L2 or L3), and single-level PSOs can achieve an average of 30°–40° correction. 23 , 26 Xu et al 27 compared the data of patients with AS kyphotic deformity treated with single-level PSO and 2-level PSO, and pointed out that 2-level PSO had a better orthopedic effect for patients with severe thoracolumbar kyphosis and LL loss. These authors also noted that although operation time and intraoperative blood loss were greater for 2-level osteotomy than for single-level osteotomy, there was no significant difference in the incidence rate of complications between the two groups.…”
Section: Discussionmentioning
confidence: 99%